Congenital ocular counter-roll: a review of cases treated exclusively by ophthalmologists - Zhu, Bin-Bin; Yan, Jian-Hua (International journal of ophthalmology, 2021)
AIM: To review the demographics, clinical manifestations, and surgical experiences of patients with congenital ocular counter-roll, whose treatments were performed exclusively by ophthalmologists. METHODS: A retrospective review was conducted consisting of patients who received strabismus surgery between 2017 to 2019. Patients with obvious ocular counter-roll were included. RESULTS: A total of 7008 patients who received strabismus surgery, 28 (12 males, 16 females) were diagnosed as congenital ocular counter-roll, accounting for 0.40%. All patients were initially misdiagnosed: 21 patients were misdiagnosed as superior oblique palsy (SOP), 3 as inferior oblique overaction, 2 as dissociated vertical deviation (DVD), 1 as superior oblique overaction with A-pattern exotropia, and 1 as medial rectus palsy. The mean±SD age was 12.4±9.4y (range 2.5-36y). The most common clinical findings included ocular counter-roll, vertical deviation or vertical deviation combined with outward deviation and head tilt. At follow-up, an excellent surgical result was achieved in 20 patients. Preoperative horizontal deviation of 26±24 prism diopter (PD) and vertical deviation of 18±12 PD were reduced to 0±12 PD (P=0.0001) and 3±4 PD (P=0.001), respectively. CONCLUSION: Congenital ocular counter-roll is a rare supranuclear vertical strabismus caused by congenital abnormalities involving vestibule-ocular reflex pathways. In addition to ocular counter-roll, the most salient clinical features included, but are not limited to, hyperdeviation, outward deviation, overelevation in adduction and head tilt.